The role of lexical expertise in reading homophones. Issue 7 (2nd July 2016) - Burt, Jennifer S.; Jared, Debra
Abstract : In Experiment 1, university students classified on lexical expertise on the basis of spelling plus nonword pronunciation accuracy made lexical decisions to homophones and control words. Homophones were accepted as words more slowly than control words, but lexical experts showed a smaller homophone cost than the less skilled group. In Experiment 2, similarly classified groups showed a large difference in their ability to detect homophones, with the low-expertise group showing a yes bias to high-frequency words, and having difficulty detecting homophones when mate-frequency was low. The results suggest superior use of orthography in the lexical experts and more reliance on semantic information in nonexperts, and support the importance of facility with orthography–phonology mappings in lexical expertise.